Analisis Faktor-Faktor Yang Mempengaruhi Kelemahan Pengendalian Internal Pemerintah Daerah(Studi Kasus Pada Kabupaten dan Kota di Provinsi Jawa TengahTahun 2013-2014) - Ppurniasari, Cici, Drs. Atwal ArifinM.Si., Ak (2016)
The study entitle "an Analysis of the Factors that Affecting Internal Control Weakness of Local Government (case Study in the District and the City of Central Java Province in the Period 2013-2014)". The purpose of this study examines of the size, economy growth, PAD, and capital expenditures of the local government to internal control weaknesses. The population in this study is the district and city of Central Java province. They are 35 regencies and cities as samples of this research. The sampling technique used purposive sampling. The secondary data are used in this study . It's sourced from www.bpk.go.id, www.bps.go.id and www.djpk.go.id. The hypothesis is tested by multiple linear regression analysis. The results of the research indicated that size, PAD, and the capital expenditures have no effect on internal control weaknesses. While Economy Growth have significantly affect on internal control weaknesses. Keywords: Internal Control Weaknesses, Size, Economic Growth, PAD, and Capital Expenditures.